Contralateral Transfalcine Versus Ipsilateral Anterior Interhemispheric Approach for Midline Arteriovenous Malformations: Surgical and Anatomical Assessment - García-García, Sergio (World Neurosurg, 2018)
BACKGROUND: The contralateral anterior interhemispheric approach (CAIA) is considered to provide surgical advantages to access deep midline lesions: wider working angle, gravity enhanced dissection and retraction, more efficient lighting, and ergonomics. Our team has previously published on the merits of using a contralateral trajectory for medial frontoparietal arteriovenous malformations (AVMs) compared with the conventional anterior interhemispheric approach (IAIA). In this article, we compare the IAIA and CAIA for the resection of medial frontoparietal AVMs using quantitative surgical and anatomical analysis. METHODS: Two models were designed mimicking the most common features of midline AVMs. The CAIA and IAIA were performed bilaterally in 10 specimens. Variables to compare technical feasibility (surgical window [SW] and surgical freedom [SF], target exposure, and angle of attack) were independently assessed using stereotactic navigation. The average SW, SF, and angle of attack were compared with the Student t test. Significance threshold was set at 0.05. RESULTS: The CITA and IAIA were similar in terms of SW, target exposure, and SF in the superior aspect of the AVM. In the depth of the interhemispheric fissure, the CAIA was significantly superior to IAIA in both AVM models: 77% wider AA for the inferior aspect of the AVM (P < 0.01) and greater SF for the draining vein (54%, P = 0.01), ipsilateral (98%, P = 0.02), and contralateral ACA (117%, P < 0.01). CONCLUSIONS: This study suggests technical superiority of the CAIA for the resection of deep midline AVMs. No objective difference was noted in the superficial areas of our models, denoting that IAIA is a safer choice for superficial AVMs. Our results set the foundation for further clinical analysis comparing both approaches.